2004
DOI: 10.1074/mcp.m400033-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Global Investigation of p53-induced Apoptosis Through Quantitative Proteomic Profiling Using Comparative Amino Acid-coded Tagging

Abstract: p53-induced apoptosis plays a pivotal role in the suppression of tumorigenesis, and mutations in p53 have been found in more than 50% of human tumors. By comparing the proteome of a human colorectal cancer cell transfected with inducible p53 (DLD-1.p53) with that of the control DLD-1 cell line using amino acid-coded mass tagging (AACT)-assisted mass spectrometry, we have broadly identified proteins that are upregulated at the execution stage of the p53-mediated apoptosis. In cell culturing, the deuterium-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 59 publications
(84 reference statements)
5
61
0
Order By: Relevance
“…Several reports dealing with identification of p53 targets in colon carcinoma cells by proteomic tools have given prominence to Annexin I in p53-mediated apoptosis (22,23); for example, proteomic analysis of mitomycin C -treated HCT 116 cells carrying wt-p53 revealed Annexin I in the group of up-regulated proteins containing p53-binding site (23). Our proteomic analysis revealed an elevated expression of this protein in treated HCT 116 cells as well.…”
Section: Discussionmentioning
confidence: 52%
“…Several reports dealing with identification of p53 targets in colon carcinoma cells by proteomic tools have given prominence to Annexin I in p53-mediated apoptosis (22,23); for example, proteomic analysis of mitomycin C -treated HCT 116 cells carrying wt-p53 revealed Annexin I in the group of up-regulated proteins containing p53-binding site (23). Our proteomic analysis revealed an elevated expression of this protein in treated HCT 116 cells as well.…”
Section: Discussionmentioning
confidence: 52%
“…Still, our results are consistent with findings from other proteomic studies. For example, Gu et al (59) observed that several glycolytic enzymes (including EnoA and GAPDH) were up-regulated at late times of death (triggered by activation of p53), and Jin et al (45) found EnoA and GAPDH in microparticles recovered from human plasma, …”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of proteins in cells exposed to hypoxia (1% O 2, 1, 3, or 6 h) was determined by mass spectrometry (MS) using the iTRAQ system of isotopic labeling for the identification and quantitation of proteins (20,21,68). In brief, 100-g protein mixtures from each treatment group (control, 1, 3, and 6 h hypoxia) were precipitated with acetone.…”
Section: Methodsmentioning
confidence: 99%